Basal Cell Adenoma of the Parotid Gland: A Case Report and Review of the Literature - AR Tootoonchian; M Sezavar; R Kahali Asl; Z nematollahi (Islamic Azad University, 2016)
Salivary gland tumors are among the pathologies in the head and neck that may be challenging in diagnosis and treatment. Most benign tumors occur in the parotid gland. Pleomorphic Adenoma is the most common type. Basal Cell Adenoma is a subtype of the Monomorphic Adenoma with rare occurrence. Proper diagnosis and clinical evaluation by the use of radiography can lead the physician to the best treatment plan for this neoplasia. Many surgical treatment modalities have been described in the literature ranging from total parotidectomy to dissection of the tumoral area alone. Extensive surgery will lead to malfunction and unacceptable esthetics due to resection of the parotid gland. One of the best approaches for treating the encapsulated and well-circumscribed pathologies is extra-capsular dissection without invading the major salivary gland. A rare case of Basal Cell Adenoma of the parotid gland in a 47-year-old female will be discussed.